Photoredox-catalyzed reaction of thianthrenium salts, sulfur dioxide and hydrazines. Issue 14 (13th June 2022) - Li, Qiangwei; Huang, Jiapian; Cao, Zenghui; Zhang, Jun; Wu, Jie
Abstract : A photoredox-catalyzed reaction of thianthrenium salts, hydrazines and DABCO·(SO2 )2 is accomplished, providing diverse arenesulfonohydrazides in moderate to good yields under mild reaction conditions. Abstract : A photoredox-catalyzed three-component reaction of thianthrenium salts, hydrazines and DABCO·(SO2 )2 is accomplished, providing facile access to diverse arenesulfonohydrazides in moderate to good yields. Broad substrate scope generality is demonstrated, and excellent functional group compatibility is observed under mild reaction conditions. A radical pathway is proposed that is initiated from thianthrenium salts irradiated with visible light.